Beginning Reading Ability: Global Method of Learning Indonesian Language Class III SDN 128/II Pasir Putih - Amadea, Meisa Aira; Aprizan, Aprizan; Aldino, Aldino (Master of Pedagogy and Elementary School Learning, 2025)
Classroom action research on third-grade students at SDN 128/II Pasir Putih, which was based on observations that initially many students were still unable to read well, can be seen from the average reading test scores of students in Indonesian language learning, which was 60%. This average score is still below the school's established learning objective achievement criteria (KKTP) of 70. This indicates that students' basic reading skills in Indonesian language learning are still insufficient. Therefore, the teaching method that can improve students' basic reading skills is the Global method. This study aims to ascertain how well the Global method in Indonesian language instruction improves students' foundational reading abilities in each cycle and how motivated they are to learn the language.  Classroom action research (CAR) was the research methodology employed.  Two cycles of the research were carried out, with each cycle including planning, carrying out, observing, and reflecting.  Twenty third-graders at SDN 128/II Pasir Putih served as the research subjects.  This study employed testing, documentation, and observation as data gathering methods and tools.  Reading assessments, teacher and student observation sheets, and written examinations in the form of LKPD were among the tools utilized in the study to collect data.  The study's findings include the following: 1) the Global method's application in Indonesian language instruction was rated as good; and 2) students' learning progressed in each cycle following the use of the Global method.  In cycle I, the initial reading skills phase was 50% complete.  In contrast, cycle II's reading proficiency was 80%.  This indicates that students learning Indonesian language chapter 1 about living things have improved their beginning reading skills from cycle I to cycle II.  When the Global technique is used, pupils' beginning reading abilities are enhanced and they have a better understanding of words and sentences before dissecting them into their constituent syllables and letters